Gambaran Umur dan Paritas pada Kejadian KEK - Umu Hani; Luluk Rosida (JHeS (Journal of Health Studies), 2018)
This study aims to determine the description of age and parity in pregnant women with KEK in Puskesmas Kasihan II Bantul Yogyakarta. The type of research is descriptive, using secondary data. Based on the results of the study of 72 pregnant women who experienced KEK there were 6 people (8.3%) who were 20 years old 35 years old or included in high risk age category, and as many as 66 people (91.7%) aged 20- 35 years or in category not at risk. Based on the results of the study of 72 pregnant women who experienced KEK there were 13 people (18.1%) who gave birth ≥ 2 times, and as many as 59 people (81.9%) who had never given birth (first pregnancy) and gave birth for the first time.